Peramalan Jumlah Produksi Jagung Kabupaten Pasaman Menggunakan Metode Pemulusan Eksponensial Tripel Tipe Brown - Destia, Atika; Helma, Helma (Journal of Mathematics UNP, 2024)
Corn is one of the most important carbohydrate-producing food crops in the world besides wheat and rice. Nowadays, corn has also become an important component of animal feed. Demand for corn continues to increase, responding to this condition, estimates of the amount of corn production in the future are needed. The aim of this research is to form a forecasting model for the amount of corn production in Pasaman Regency using the Brown type triple exponential smoothing method and predict the amount of corn production in Pasaman Regency from 2023-2025 based on the model that has been formed.This type of research is applied research with secondary data collection. In this study secondary data was obtained from the official website of the Pasaman Regency Central Statistics Agency. From the forecasting model, it can be seen that the parameter value α=0.26 can minimize the MSE value so that the forecast results in 2023 are 114,939.6 tons, in 2024 it is 123,762.4 tons, and in 2025 it is 132,762.4 tons.